Exposure of domestic animals to Mayaro and Oropouche viruses in urban and peri-urban areas of West-Central Brazil - Helver Gonçalves Dias; Débora Familiar-Macedo; Ingrid Oliveira Garrido; Flávia Barreto dos Santos; Alex Pauvolid-Corrêa (BMC, 2024)
Abstract Oropouche and Mayaro viruses are enzootic arboviruses of public health concern throughout Latin America. Recent outbreaks of OROV in northern region and sporadic autochthonous cases in western region of Brazil, suggest a silent circulation of these neglected viruses. Aiming to investigate the exposure of different species of domestic animals to MAYV and OROV in urban and peri-urban areas of West-Central Brazil, we performed a cross-sectional serosurvey by plaque reduction neutralization test (PRNT). Our findings included neutralizing antibodies for both arboviruses in cattle, dogs and horses, suggesting eventual role of domestic animals in enzootic arbovirus surveillance in Brazil.